Odpowiedzi

  • Użytkownik Zadane
2009-12-05T18:12:31+01:00
A) ¾ + ¹⁶/₉ ÷ 0.9 = ¹⁹/₁₃ ÷ ⁹/₁₀ = ¹⁹/₁₃ × ¹⁰/₉ = ¹⁹⁰/₁₁₇ = 1⁷³/₁₁₇

b) ⁸/₁₀ × (³/₂)² + 2³ ÷ 4 × ¹/₁₀ = ⁸/₁₀ × ⁹/₄ + 8 ÷ ⁴/₁₀ = ⁷³/₄₀ + 8 × ¹⁰/₄= ⁷³/₄₀ + ⁸⁰/₄ = ¹⁵³/₄₄ = 3²³/₄₄

c) (⁴/₃)² × ¹/₉ - 1 × 3 = ¹⁶/₉ × ¹/₉ - 3 = ¹⁶/₈₁ - 3
1 5 1
2009-12-05T19:36:36+01:00
A) ¾ + ¹⁶/₉ ÷ 0.9 = ¹⁹/₁₃ ÷ ⁹/₁₀ = ¹⁹/₁₃ × ¹⁰/₉ = ¹⁹⁰/₁₁₇ = 1⁷³/₁₁₇

b) ⁸/₁₀ × (³/₂)² + 2³ ÷ 4 × ¹/₁₀ = ⁸/₁₀ × ⁹/₄ + 8 ÷ ⁴/₁₀ = ⁷³/₄₀ + 8 × ¹⁰/₄= ⁷³/₄₀ + ⁸⁰/₄ = ¹⁵³/₄₄ = 3²³/₄₄

c) (⁴/₃)² × ¹/₉ - 1 × 3 = ¹⁶/₉ × ¹/₉ - 3 = ¹⁶/₈₁ - 3
1 5 1